2012
DOI: 10.1159/000345080
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Lattice Fluoride Effects on the Solubility and Crystallinity of Carbonated Apatites with Incorporated Fluoride

Abstract: The purpose of this study was to evaluate quantitatively the effects of fluoride on the solubility and crystallinity of carbonated apatites (CAPs) after its incorporation into the crystal lattice using the metastable equilibrium solubility (MES) distribution method. Fluoride-incorporated CAPs (F-CAPs) of two different carbonate levels (3 and 5%) and fluoride contents from 0 to 20,000 µg/g were synthesized. X-ray diffraction experiments and Rietveld analysis were conducted to obtain crystallite microstrain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…IAP FAP in all fluoridated tests also stabilizes by 144 h. IAP FAP for the 30 mg-F/L tests plateaus more quickly after 10 h and drops slightly after 144 h, consistent with exhibiting FHAP solubility that decreases with increased F – as a fraction of X sites (or F – fraction). Compared to a similarly high-solubility FAP, the solutions are slightly supersaturated and appear to be slowly converging toward that solubility. Therefore, the K s0 ’s of HAP and FAP from Zhu et al are appropriate reference points for the HAP in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IAP FAP in all fluoridated tests also stabilizes by 144 h. IAP FAP for the 30 mg-F/L tests plateaus more quickly after 10 h and drops slightly after 144 h, consistent with exhibiting FHAP solubility that decreases with increased F – as a fraction of X sites (or F – fraction). Compared to a similarly high-solubility FAP, the solutions are slightly supersaturated and appear to be slowly converging toward that solubility. Therefore, the K s0 ’s of HAP and FAP from Zhu et al are appropriate reference points for the HAP in this study.…”
Section: Resultsmentioning
confidence: 99%
“…XRD of postfluoridated HAP did not indicate the presence of any phase other than apatite (Figure S4a). HAP and FAP share the same diffraction patterns except for peak shifts largely indicative of a change in unit cell size (Δ V / V = 1.3%) due to differences in the size and lattice position of F – and OH – ions. ,, This feature has been used to quantify F – incorporation in FHAP solid solutions where the a unit cell dimension decreases linearly with increased F – fraction while the c dimension remains relatively constant. ,, Using the Rietveld method, refined a and c parameters of fluoridated samples were plotted against F – fraction in Figure S4b. The a dimension decreased with increased F – fraction, while c did not change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Te apatite (HA, FHA, and FA) powders were manufactured in-house, in accordance with the methods previously described [18,19]. After synthesis, the powders were characterized using x-ray difraction (XRD), inductively coupled plasma-mass spectroscopy (ICP-MS), and Fourier-transform infrared spectroscopy (FTIR) to confrm the apatite structure [14].…”
Section: Device Coatingsmentioning
confidence: 99%
“…The process of fluoridisation imposes changes in the apatite structure, expressed by decreasing apatite unit cell a-axis value with the increase of fluoride content. Apart from the shortening along a-axis, it was reported that fluoride incorporation into the carbonate-and xydroxylapatite mineral lattice increases the mineral crystallinity in the direction of the longest caxis of the crystallite, the amount of crystallographic microstrain, the solubility and the optical birefringence (Qiao et al, 2017;Wopenka and Pasteris, 2005;Yan et al, 2013).…”
Section: Crystallite Size Estimationmentioning
confidence: 99%